Optimizing Reservoir Water Management in a Changing Climate - Beça, Pedro (2023)
Funding Information: Open access funding provided by FCT|FCCN (b-on). This research was partially funded by the collaborative international Consortium INNOMED financed under the ERA-NET WaterWorks2015 co-funded Call, an integral part of the 2016 Joint Activities developed by the Water JPI. The authors P.B. and J.P.N. acknowledge the support from CHANGE—Global Change and Sustainability Institute, Faculty of Sciences, University of Lisbon (FCUL/ULisboa), Portugal. Publisher Copyright: © 2023, The Author(s).